2016
DOI: 10.15441/ceem.15.109
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of bedside ultrasonography reduce emergency department length of stay for patients with renal colic?: a pilot study

Abstract: ObjectiveThe aim of this study was to evaluate the effect of adding bedside ultrasonography to the diagnostic algorithm for nephrolithiasis on emergency department (ED) length of stay.MethodsA prospective, randomized, controlled pilot study was conducted from October 2014 to December 2014 with patients with acute flank pain. In the non-ultrasonography group (NUSG), non-contrast computed tomography was selected based on clinical features and hematuria in the urinalysis. In the ultrasonography group (USG), non-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 14 publications
(20 reference statements)
0
9
0
1
Order By: Relevance
“…The importance of POCUS in evaluating patients with renal colic is being increasingly recognized [17,18]. However, only a few ultrasonography algorithms for managing patients suspected with ureter stone exist [19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of POCUS in evaluating patients with renal colic is being increasingly recognized [17,18]. However, only a few ultrasonography algorithms for managing patients suspected with ureter stone exist [19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, one large ( n = 2759) study, randomising patients into diagnosis through EP PoCUS, radiologist ultrasound or computed tomography (CT), found no difference in high-risk diagnoses that could be due to missed or delayed diagnosis after 30 days, and showed overall lower cumulative radiation exposure at 6 months for both ultrasound groups compared to the CT group [116]. They also showed a slight, but significant, reduction in ED length of stay, while another study found halving of the length of stay [117].…”
Section: Resultsmentioning
confidence: 99%
“…Patients presenting with acute renal colic at the emergency department Authors Year Country Study design No. of patients % Male Mean age ± SD (years) Kim et al [ 13 ] 2018 South Korea Retrospective, observational 798 68.6 48.2 ± 13.3 Desai et al [ 14 ] 2018 USA Retrospective, observational 350 NR NR Türk and Ün [ 15 ] a 2017 Turkey Prospective, observational 516 60.5 37 ± 20.3 Shrestha et al [ 16 ] a 2017 Nepal Retrospective, observational 201 55.2 29 ± 13.5 Odoemene et al [ 17 ] a 2017 Nigeria Prospective, observational 69 76.8 40.4 ± 2.9 Mefford et al [ 18 ] 2017 USA Retrospective, observational 393 69 Median 43 (IQR 32–54) Rapp et al [ 19 ] 2016 USA Retrospective, observational 613 47 49 ± 0.6 Park et al [ 20 ] 2016 South Korea Prospective, RCT 103 66 45.6 ± 12.55 Hernandez et al [ 21 ] 2016 USA Retrospective, observational 536 56 45.9 ± 16.3 <...>…”
Section: Resultsmentioning
confidence: 99%